2014
DOI: 10.15837/ijccc.2014.6.1480
|View full text |Cite
|
Sign up to set email alerts
|

Representing IT Performance Management as Metamodel

Abstract: Many empirical studies have shown that the business value from investment in IT projects can be greater than the one being currently achieved. Thus it calls for specific focus on IT governance in order to reach fusion between business and IT goals. Good IT performance management should enable the business and IT executives to understand how IT is contributing to the achievement of business goals. The paper addresses the issue of representing IT governance best practice frameworks as ontological metamodels. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Accordingly, the two principal families of KPIs usually used refer to the efficiency and effectiveness of IT in supporting the business. Although there is a large number of best practices and methods for measuring IT performance, problems still occur when traditional financial measures are simply applied to IT [2]. The ability to make wellinformed IT decisions requires an in-depth knowledge of IT processes and dedicated KPIs.…”
Section: Performance Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the two principal families of KPIs usually used refer to the efficiency and effectiveness of IT in supporting the business. Although there is a large number of best practices and methods for measuring IT performance, problems still occur when traditional financial measures are simply applied to IT [2]. The ability to make wellinformed IT decisions requires an in-depth knowledge of IT processes and dedicated KPIs.…”
Section: Performance Managementmentioning
confidence: 99%
“…involves the leadership and organizational structures and processes required to ensure that the organization's IT sustains and aligns with the organization's strategies and objectives" (IT Governance Institute, 2011). As such, the development and implementation of a framework for IT governance is central for modern enterprises [2]. IT governance thus warrants dedicated and continuous attention to assess and improve operations [3].…”
Section: Introductionmentioning
confidence: 99%
“…Many empirical studies have shown that the business value from IT projects investments can be greater than the one being currently achieved [22]. Organizations that value project management as the strategic capability that drives change already perform better than their counterparts [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As Pajic et al [2] highlight the increasing use of information technology has resulted in firms needing to evaluate the productivity impact of IT investments through IT value measures [2]. However, IT value has been a continuous discussion for organisations.…”
Section: Introductionmentioning
confidence: 99%